Examining educational attainment and allostatic load in non-Hispanic Black women - Brittany Marie Williams; Christian Laurent; Rishab Chawla; Justin Xavier Moore (BMC, 2022)
Abstract Background Research suggests that non-Hispanic Black (henceforth, Black) women and people with lower educational attainment have higher levels of allostatic load (AL). This study sought to determine the association between educational attainment and AL among a large sample of Black women. Methods We analyzed data among 4177 Black women from the National Health and Nutrition Examination Survey years 1999-2018. AL score was defined as the total for abnormal measures of eight biomarkers. We further categorized participants with AL score greater than or equal to 4 as having high AL. We calculated mean estimates of total allostatic load scores using generalized linear models. We performed modified Poisson Regression models with robust variance estimation to estimate prevalence ratios (PRs) of high allostatic load and their associated 95% confidence intervals (CIs) by educational attainment. Results Black women with a college degree or higher had the lowest prevalence of high allostatic load (31.8% vs. 42.7%, 36.3%, 36.6%), and age adjusted mean allostatic load scores (mean = 1.90 vs. mean = 2.34, mean = 1.99, mean = 2.05) when compared to Black women with less than a high school diploma, high school diploma or GED, and some college or associates degree respectively. Even after accounting for age, poverty-to-income ratio, smoking, congestive heart failure, and heart attack, Black college graduates had an 14.3% lower prevalence of high allostatic load (PR = 0.857, 95% CI 0.839-0.876) when compared to Black women with lower educational attainment. Conclusions Black women with a baccalaureate degree or higher educational attainment had lower allostatic load compared to Black women with less than a high school education. This finding further confirms higher education is a social determinant of health. Future research should explore differences in AL by more granular degree types.